Systematic review on effectiveness of methods of delivery and reminder of health education module to improve adherence on childhood immunization schedule - Rusli, Mohammad Farhan; Juni, Muhamad Hanafiah; Mohd Zulkefli, Nor Afiah (Community Health Society Malaysia (CHSM), Universiti Putra Malaysia, 2018)
Background: There are currently various methods of delivery that can improve adherence on under-five childhood immunization schedule. The methods differ significantly and there is the conventional method of providing a health education module, reminders and recalls to improve adherence and some other non-conventional methods to improve adherence. A systematic review was conducted on the effectiveness of methods of delivery and reminder of health education module to improve adherence on childhood immunization schedule. Materials and Methods: The systematic review performed utilized searched on available electronic databases and bibliographies of studies and also previous reviews. The databases were broad search and began with the use of generic terms to identify search terms that were relevant. The PRISMA (Preferred Reporting Items for Systematic Review and MetaAnalysis) by Moher et al (2009) was used. Databases including PubMed, Science Direct, Medline and CINAHL were utilized for this systematic review. Results: The studies in the review conducted was conducted in various countries with the United States of America (USA) contributing 7 studies, followed by the United Kingdom and Pakistan with 3 studies each and Kenya, Australia, New Zealand and India with 1 study respectively. The lowest number of respondents was 12 while the most was 9213 respondents. All studies were Randomized Control Trial’s (RCT’s) and 1 Quasi Experimental study. Conclusion: The studies showed multiple factor and effective methods of delivery with reminders for health education. Utilizing technology showed to be one of the most effective methods.